(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The paper presents the results of a study about information management, information technology management and behaviors and values concerning information in Brazilian institutions of higher education. The ‘information orientation’ (IO) model, developed by Donald A. Marchand, William J. Kettinger and John D. Rollins (2000) was adopted as a conceptual basis for the study. The data was collected through questionnaires filled by 83 (eighty-three) managers of higher education institutions (HEI) located in Belo Horizonte, Brazil. The results show that, as perceptions of their managers, HEI are oriented towards information, although this guideline varies according to the dimensions of the construct of the HI Model, which has as central information management, information technology and informational values and behaviors. It was noted that the managers of HEI perceive each of these elements, there is a predominance of HEI Information Technology. Keywords: Information Orientation. Information Management. Information Technology. Education. Information Culture. Information Behavior. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3123/2458